Sitagliptin Reduces Endothelial Dysfunction and Apoptosis Induced by High-Fat Diet and Palmitate in Thoracic Aortas and Endothelial Cells via ROS-ER Stress-CHOP Pathway - Cao, Qiongqiong; Xu, Dongmei; Chen, Yong; Long, Yueming; Dai, Fang; Gui, Li; Lu, Yunxia (Frontiers in Pharmacology, 2021)
Macrovascular disease is tightly associated with obesity-induced metabolic syndrome. Sitagliptin (SIT), an orally stable selective inhibitor of Dipeptidyl peptidase-4 (DPP-4), has protective effects on endothelium. However, the mechanisms enabling SIT to exhibit resistance to diet-induced obesity (DIO) related with reactive oxygen species (ROS) and endoplasmic reticulum (ER) stress in the aorta and endothelial cells have not been reported yet. Therefore, the present study was conducted to determine if SIT exerts protective role in the thoracic aortas isolated from the high-fat diet (HFD)-treated rats and palmitate (PA)-treated endothelial cells by alleviating ROS and ER stress. Male Sprague Dawley rats were randomly divided into standard chow diet (SCD), HFD and HFD plus sitagliptin administration (HFD+SIT) groups. The rats of latter two groups were given HFD fodder for 12 weeks, then the HFD+SIT rats were treated with SIT (10 mg/kg/d) by intragastric administration for another 8 weeks. The body mass, vascular tension, serum oxidative stress indices and inflammatory parameters, pathological changes, protein expression of endothelial nitric oxide synthase (eNOS), the genes associated with ER stress and apoptosis in the thoracic aorta were measured. Furthermore, cell proliferation, ROS and the protein expression associated with ER stress (especially CHOP) and apoptosis were assessed in human umbilical vein endothelial cells (HUVECs) incubated with SIT and PA. Compared to the SCD rats, the HFD rats had higher serum lipid levels, decreased vascular tension, increased inflammation, oxidative and ER stress, and apoptosis of endothelial cells. PA promoted ROS generation, ER stress and apoptosis, inhibited cell proliferation in HUVECs. SIT treatment obviously ameliorated apoptosis via alleviating ROS and ER stress in the thoracic aortas isolated from HFD-fed rats and PA-treated HUVECs. The results suggest that SIT improved endothelial function via promoting cell proliferation and alleviating ROS-ER stress-CHOP pathway both in vivo and in vitro.